TUGAS DAN FUNGSI KEPALA DESA MADANI DALAM PENGELOLAAN KEUANGAN DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Anthon Sattu Pabesak; Yoseph Pasolang (LPPM Universitas Ekasakti, 2024)
This study aims to understand the roles and functions of village heads in managing the finances of Madani Village and the factors influencing them. The village, as the lowest administrative unit, plays a strategic role in development and public service provision as stipulated by Law No. 6 of 2014. Public accountability is the main foundation in village governance. This research uses a descriptive analytical method with normative and empirical legal approaches. Data were collected through interviews and documentation studies at the Madani Village Office, Wotu District, East Luwu Regency. The results show that village heads hold significant positions in carrying out governance, development, and community guidance. Financial management in the village faces several issues such as delayed payments and asset management. Improvement efforts are made through monitoring, evaluation, and enhancing financial management practices. Implementing public accountability principles is necessary to improve transparency and the performance of village governance.